Estimating the Proportion of People Living With HIV Who May Benefit From the Reverse Algorithm for the Diagnosis of Incident Syphilis - Menza, Timothy W; Berry, Stephen A; Dombrowski, Julia C; Cachay, Edward; Crane, Heidi M; Mayer, Kenneth H (Sexually transmitted diseases, 2024)
Among 8455 people engaged in HIV care in 4 US cities, 4925 (58%) had treponemal testing at care entry. Of the 4925 tested, 3795 (77%) had a nonreactive result and might benefit from the reverse algorithm for a future incident syphilis diagnosis. Furthermore, low-barrier treponemal testing as a first step in the reverse algorithm may increase syphilis screening and decrease time to treatment.